Properties of various plasma surface treatments for low-temperature Au–Au bonding. (23rd March 2018) - Yamamoto, Michitaka; Higurashi, Eiji; Suga, Tadatomo; Sawada, Renshi; Itoh, Toshihiro
Abstract: Atmospheric-pressure (AP) plasma treatment using three different types of gases (an argon-hydrogen mixed gas, an argon-oxygen mixed gas, and a nitrogen gas) and low-pressure (LP) plasma treatment using an argon gas were compared for Au–Au bonding with thin films and stud bumps at low temperature (25 or 150 °C) in ambient air. The argon-hydrogen gas mixture AP plasma treatment and argon LP plasma treatment were found to distinctly increase the shear bond strength for both samples at both temperatures. From X-ray photoelectron spectroscopy (XPS) analysis, the removal of organic contaminants on Au surfaces without the formation of hydroxyl groups and gold oxide is considered effective in increasing the Au–Au bonding strength at low temperature.